The Influence of Nanohydroxyapatite on the Thermal, Mechanical, and Tribological Properties of Polyoxymethylene Nanocomposites - Kinga Pielichowska; Dariusz Bieliński; Michał Dworak; Ewelina Kilian; Beata Macherzyńska; Stanisław Błażewicz (International Journal of Polymer Science)
The influence of nanohydroxyapatite on the glass transition region and its activation energy, as well as on the tribological and mechanical properties of polyoxymethylene nanocomposites, was investigated using DMA, TOPEM DSC, nanoindentation, and nondestructive ultrasonic methods. It was found that the glass transition for unmodified POM was in the lower temperature range than in POM/HAp nanocomposites. Moreover, ΔCp and activation energy were larger for POM/HAp nanocomposites. Friction coefficient was higher for POM/HAp nanocomposites in comparison to both POM homopolymer and POM copolymer. Simultaneously, the indentation test results show that microhardness is also higher for POM/HAp nanocomposites than for POM. From ultrasonic investigations it was found that the highest values of both longitudinal and transverse propagation waves and Young’s and shear modulus for POM homopolymer (DH) and POM copolymer T2H and their nanocomposites can be attributed to their higher degree of crystallinity in comparison to UH copolymer. Moreover, for POM/HAp nanocomposites with 5% of HAp, ultrasonic longitudinal wave velocity was almost constant even after 1000000 mechanical loading cycles, evidencing an enhancement of mechanical properties by HAp nanoparticles.